Etiology of cerebral palsy in children below age of 5 years - Kasundra, Mitul; Patel, Purvi; Mehariya, K. M. (International Journal of Contemporary Pediatrics, 2020)
Background: Cerebral palsy is the most common and costly form of chronic motor disability that begins in childhood. Aims of the study were to identify etiology and risk factors of CP*, to find correlation between the etiology and clinical type of CP* in children below age of 5 years. Methods: analytical study done in indoor patients at civil hospital, Ahmedabad from October 2014 to September 2016. Results: Overall incidence of cerebral palsy in indoor patients was 0.78 per 100 patients. Most common age of presentation is 1-3 years. Majority of cases have perinatal factors as etiology followed by postnatal etiology. Most common type of CP was spastic type. Most common type of topographical CP was spastic quadriplegic. Major symptom for which they admitted in the hospital was convulsion. Conclusions: Majority of cases had perinatal factors as etiology author can prevent CP* by providing primary prevention, specific prevention and improving antenatal and intra-natal care. Disease progression of CP* can be halted by secondary prevention. Maximization of function can be done by tertiary prevention.